Engine performance, emission, and sustainability analysis with diesel fuel-based Shorea robusta methyl ester biodiesel blends - Rai R.K.; Sahoo R.R. (My University, 2025)
The effect of compression ratio (CR), engine load, and blend percentage of biodiesels (10, 20, 30, 40% v/v.) on the energy, emissions, exergy, and sustainability parameters of an engine has been investigated in the present experimental study. Results revealed that with escalating the engine load, compression ratio, and the percentage of Shorea robusta methyl ester (SRME) in diesel fuel, the effective efficiency (BTE), exergetic efficiency, exergy destruction rate, and engine sustainability were enhanced. The BTE and exergy efficiency of the engine with diesel fuel has 7.39%, 5.43%, 4.60% and 1.57% higher values than 40%, 30%, 20%, and 10% SRME blended fuel, respectively at 1500 rpm engine speed with 100% engine load. However, the NO, unburned hydrocarbon (UHC), and carbon monoxide (CO) emission levels were found enhanced with CR and engine load. Also, with an increase in the percentage of SRME blends, the NO level has been enhanced and the UHC, CO levels were found reduced. The NO emission of the engine with diesel fuel has 66.53%, 40.61%, 14.28%, and 10.20% lower values than 40%, 30%, 20, and 10% SRME fuel blend at a compression ratio of 17 with engine full load. The use of SRME biodiesel blends improved the combustion phenomenon of fuel without any significant drop in the performances and sustainability index of the engine. Therefore, the experimental investigation approved the SRME based diesel blend fuel has an intense possibility to be a substitute for the standard fuel without any alteration of engine design. © 2021 Elsevier Ltd